Religious Reconquest, Social Commitment and Marks of Secularisation in relationes ad limina of some Spanish Bishops (1947-57) - Baruzzo, Enrico (JoMaCC, 2022)
The essay examines the relationes ad limina written by some Spanish bishops between 1947 and 1957. In these documents the bishops deal with the pastoral action carried out to restore Catholicism to Spain after the years of the Second Republic and the civil war and they describe the intense social commitment promoted since the end of the 1940s to combat illiteracy and misery of workers and peasants. They also report behaviours and data that highlight a growing secularisation and contrast with the image of a compact Catholic Spain.